Religious Platonism : the influence of religion on Plato and the influence of Plato on religion - Feibleman, James K. (James Kern), 1904-1987 (Routledge library editions. Philosophy of religion, 2013)
First Published in 1959. Routledge is an imprint of Taylor & Francis, an informa company.